Studi Kelayakan Pengadaan Alat Picture Archiving and Communication System di RSUP Dr. Soeradji Tirtonegoro Klaten - Retno Dyah Parwitasari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
This study aimed to analyze the appropriateness of the technical aspects, the financial markets and the procurement plan PACS.Penelitian this is a case study located at the General Hospital Center (Dr) Soeradji Tirtonegoro Klaten. This study found that investment decisions PACS instrument in terms of the technical aspects and the market has met. From the aspect of finance, investment appraisal results using PP is 2 years 239.4 days, less than a specified useful life, which is 5 years means that investment is worth it. The results of the NPV method is Rp.1.875.508.315,25, meaning that the investment is worth it. The results of the method IRR is 27%, greater than the specified rate of return of 6.5%, meaning that the investment is worth it. Thus we can conclude the investment project in the PACS instrument dr. Soeradji Tirtonegoro Klaten feasible.